(untitled) (PANGEEA, 2025)
Earth planet. The material developed is aimed at a general model to presentation our planet in the lesson of Geography. They are presented interactively information about the universe, solar system components, geographical coordinates, movements and representations of Earth, so understanding these concepts is much easier. The lesson is accompanied by a series of animations, diagrams, interactives and images from each chapter and activity evaluation at the end.